CMV Enteritis Causing Massive Intestinal Hemorrhage in an Elderly Patient - Mihaiela Morunglav; Ivan Theate; Gilles Bertin; Philippe Hantson (Case Reports in Medicine)
Background. Cytomegalovirus (CMV) disease is rare in previously immunocompetent patients. We report a case of CMV enteritis complicated by massive intestinal bleeding. Case History. A 72-year-old immunocompetent patient was admitted for diarrhea and abdominal pain. Aspecific pattern of duodenitis was found at abdomen computed tomography and on biopsies during endoscopy. A diagnosis of vasculitis was suspected on the basis of the clinical and biological course (skin lesions, arthralgias, proteinuria, low complement C3 and C4 fractions, etc.) and pulse steroid therapy was prescribed. The patient developed multiple episodes of intestinal bleeding with shock and required urgent laparotomy. Jejunitis due to CMV vasculitis was proven by histological examination of the operative specimen. Treatment with ganciclovir was initiated. No bleeding recurrence was noted. No other lesions from CMV infection were observed. The patient died from unrelated complications. Discussion. CMV enteritis is a rare cause of intestinal bleeding particularly in previously immunocompetent patients. Aging could be accompanied by a relative immune weakness and specific antiviral therapy seems to be indicated.